Hypersensitivity Pneumonitis: Challenges in Diagnosis and Management, Avoiding Surgical Lung Biopsy - Morell, Ferran; Villar, Ana; Ojanguren, Iñigo; Muñoz, Xavier; Cruz, María-Jesús (Seminars in Respiratory and Critical Care Medicine, 2016)
This review presents an update of the currently available information related to hypersensitivity pneumonitis, with a particular focus on the contribution of several techniques in the diagnosis of this condition. The methods discussed include proper elaboration of a complete medical history, targeted auscultation, detection of specific immunoglobulin G antibodies against the most common antigens causing this disease, skin tests, antigen-specific lymphocyte activation assays, bronchoalveolar lavage, and cryobiopsy. Special emphasis is placed on the relevant contribution of specific inhalation challenge (bronchial challenge test). Surgical lung biopsy is presented as the ultimate recourse, to be used when the diagnosis cannot be reached through the other methods covered.
Keywords: hypersensitivity pneumonitis; bronchoalveolar lavage; specific inhalation challenge; bronchial challenge test; precipitins; cryobiopsy; skin test